Переменность планетарных туманностей. Результаты многолетних наблюдений - Кондратьева, Л. Н.; Денисюк, Э. К.; Шомшекова, С. А.; Рева, И. В.; Айманова, А. К.; Кругов, М. А.
Представлены результаты спектроскопических и фотометрических наблюдений 14 компактных планетарных туманностей. Наблюдения проводились в Астрофизическом институте им. В.Г. Фесенкова (Казахстан) с 1973 г. The results of spectroscopic and photometric observations of 14 compact planetary nebulae are presented. The observations were carried out at the Fesenkov Astrophysical Institute (Republic of Kazakhstan) since 1973 Our goal was to obtain data on the variability of our objects over long-time intervals.
Keywords: Астрофизика